Vibration Mitigation of Wind Turbine Towers Using Negative Stiffness Absorbers. (5th June 2021) - Kapasakalis, Konstantinos A.; Antoniadis, Ioannis A.; Sapountzakis, Evangelos J.; Kampitsis, Andreas E.
No abstract available